Paul Hiebert’s Worldview Model: Understanding Cultural Encounters - Sharma, Manju (Himalayan Journal of Sociology and Anthropology, 2012)
According to Paul Hiebert, worldview is a set of our assumptions which lies in the core of a culture. Worldviews provide us cognitive foundation, validate our norms, and give emotional security. His worldview model has three dimensions: cognitive, affirmative and evaluative. Cognitive dimension relates to the knowledge which guides us to perceive the reality of self and surroundings. Affirmative dimension relates to our feelings, emotions, and behavior. So we react to the action on the basis of our feelings. Likewise evaluative dimension relates to the judgment - what is right and wrong. This paper discusses how his worldview model can be used to understand encounters among the cultures. Further, it explores how culture affects the construct of social reality and vice versa. It also investigates how it is useful to theorize concepts of 'us' and 'them'. DOI: http://dx.doi.org/10.3126/hjsa.v5i0.7041 Himalayan Journal of Sociology & Anthropology-Vol. V (2012) 82-94